The open innovation research landscape: established perspectives and emerging themes across different levels of analysis. Issue 1 (24th November 2016) - Bogers, Marcel; Zobel, Ann-Kristin; Afuah, Allan; Almirall, Esteve; Brunswicker, Sabine; Dahlander, Linus; Frederiksen, Lars; Gawer, Annabelle; Gruber, Marc; Haefliger, Stefan; Hagedoorn, John; Hilgers, Dennis; et al.
Abstract: This paper provides an overview of the main perspectives and themes emerging in research on open innovation (OI). The paper is the result of a collaborative process among several OI scholars – having a common basis in the recurrent Professional Development Workshop on 'Researching Open Innovation' at the Annual Meeting of the Academy of Management. In this paper, we present opportunities for future research on OI, organised at different levels of analysis. We discuss some of the contingencies at these different levels, and argue that future research needs to study OI – originally an organisational-level phenomenon – across multiple levels of analysis. While our integrative framework allows comparing, contrasting and integrating various perspectives at different levels of analysis, further theorising will be needed to advance OI research. On this basis, we propose some new research categories as well as questions for future research – particularly those that span across research domains that have so far developed in isolation.